In situ photoinitiated fabrication of phosphorylcholine-functionalized polyhedral oligomeric silsesquioxane hybrid monolithic column for mixed-mode capillary electrochromatography. Issue 10 (5th May 2022) - Lei, Xiaoyun; Zhang, Bingyu; Zhang, Yi; Huang, Ting; Tang, Fengxiang; Wu, Xiaoping
Abstract : A phosphorylcholine-functionalized POSS hybrid monolithic column was synthesized via UV curing. It exhibits hydrophilic interaction and weak cation exchange chromatography retention mechanism for the separation of typical polar and charged compounds. Abstract : A monolithic-based mixed-mode stationary phase was prepared for capillary electrochromatography via the fast photoinitiated polymerization of 2-methacryloyloxyethyl phosphorylcholine and polyhedral oligomeric silsesquioxane methacrylate (POSS-MA) monomers in the presence of crosslinker pentaerythritol triacrylate (PETA). Several copolymerization parameters, including the composition of monomers or porogens, ratio of crosslinkers to monomers, and polymerization time, were systematically optimized to tune the permeability and efficiency of monolithic columns. The morphologies and structures of the as-prepared monoliths were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy, thermogravimetry and nitrogen adsorption/desorption analysis, indicating a typical POSS skeleton morphology with numerous mesopores on the monolith. Owing to the incorporation of zwitterionic functional groups and rigid POSS skeleton on the hybrid monolith, the resulting stationary phase exhibited both hydrophilic and electrostatic interactions, as well as good mechanical stability. Pressurized CEC separation of various kinds of polar compounds such as amides, nucleobases, nucleosides and benzoic acids, and polypeptide antibiotics was achieved by mixed-mode retention mechanisms including hydrophilic interaction chromatography (HILIC) and weak cation exchange chromatography (WCX) with a high column efficiency up to 93 500 plates per m (thiourea).